Masalah Keasingan dalam Masyarakat: Suatu Reviu Integratif dalam Dimensi Politik, Ekonomi, Sosial, Pendidikan, Psikologi dan Spiritualiti: The Issue of Alienation in Society: An Integrative Review in Political, Economic, Social, Educational, Psychological, and Spiritual Dimensions - Kamari, Isa; Abdul Hamid, Faisal @ Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
The issue of alienation is a societal phenomenon that results in human life drifting away from the natural disposition set by Allah. Through an integrative review, this paper aims to unearth, filter, analyze, and refine several principles of the issue of alienation operating within the dimensions of politics, economics, social structures, education, psychology, and the spirituality of society in theory, particularly within the contextual framework experienced by the Malay community in Singapore from 1965 to the late 1990s. Understanding the issue of alienation is the initial step toward addressing it by reinstating Allah’s natural disposition into the fabric of society’s life.